A study of network bandwidth management by using queue tree with per connection queue - C. Smansub; B. Purahong; P. Sithiyopasakul; C. Benjangkaprasert (My University, 2019)
This paper presents a study of network bandwidth management by using the queue tree function with per connection queue function (PCQ). To study a bandwidth management by configuring a network system that uses a Mikrotik router and configures IP number in the network system. WinBox software is used for testing network bandwidth management by download file testing from the internet. The results show a performance of queue tree function and PCQ function for bandwidth management. All users in a network have been received an equal bandwidth of utilization network.
Keywords: Bandwidth management; Dynamic Bandwidth Allocation; Network monitoring; Network Traffic and Congestion Control